Evaluation of Moringa Peregrina (Forsk) Fiori, Leaf and Seed Extract Against Multidrug Resistant Strains of Bacteria and Fungus of Clinical Origin - Albalawi, Suliman Mansour; Al-Asmari, Abdulrahman K.; Rafatullah, Syed; Mahfoud, Maysa (Archives of Ecotoxicology, 2021)
The emergence of antibiotic resistant microorganism strains has become a critical concern in the treatment of infectious diseases and makes the search of an alternative therapy a must. The study was designed to evaluate the in vitro antimicrobial activities of the Moringa peregrina (MP) leave (MPL) and seed (MPS) extracts. Antimicrobial assays were performed using a microplate growth inhibition assay against 11 multidrug-resistant (MDR) strains. Following qualitative analysis, dose-response assays were performed using the MTT colorimetric assay. The results showed a strong correlation between the MPL and MPS extract concentration and growth inhibition (P<0.001). MP extract revealed a remarkable antimicrobial effect and inhibited the growth and survival of MDR pathogens which include Escherichia coli; Pseudomonas aeruginosa; Klebsiella pneumonia; Acinetobacter baumannii; Staphylococcus aureus between (88.6-94.7 %) and between (62.3- 88.7%) against Candida Kefyer; Candida parapsilosis; Candida albicans; Candida glabrata; Aspergillus flavus and Fusarium oxysporum. MIC50 ranging from ≤6.25 to 25 mg/mL. Acinetobacter baumannii and Pseudomonas aeruginosa were the most susceptible to MP extracts (MIC50 < 6.25 mg/mL). These results support the use of MP in Arab traditional medicine as natural antimicrobial agents. Additionally, the use of such naturally occurring adjuvant derived from medicinal plants can be used as an adjuvant with synthetic antibiotics to combat bacterial resistance and to enhance the antibacterial potential. Further studies are recommended on isolation and purification of novel antimicrobial molecules to treat the infections caused by microbes.